Elevating the interlinkages between water, energy, food, and climate at global level - McCartney, Matthew P.; Ringler, Claudia (CGIAR, 2023)
The COP28 summit concluded in Dubai this week with an historic agreement: the first ever to recognize the need to “transition away” from fossil fuels. Also agreed was the need to triple the capacity of renewables, reduce climate-induced water scarcity, enhance climate resilience to water-related hazards, reduce climate impacts on ecosystems and biodiversity, accelerate uptake of nature-based solutions, and attain climate-resilient food and agricultural production and supply.